Revolution and Disenchantment Arab Marxism and the Binds of Emancipation - Bardawil, Fadi A, 1977-; Project Muse. (Duke University Press, 2020)
"EMANCIPATION BINDS is an intellectual history of the Lebanese New Left in the late 1960s. Through deep archival work, Fadi Bardawil's analysis moves beyond the usual narrative of the reception of Marxist-Leninist thought in the postwar Middle East in order to analyze the production and circulation of critical and revolutionary theory as both a part of, and apart from, the Arab intellectual tradition. His primary interlocutor in this history is Waddah Charara, a militant intellectual pushed to the fore of the decolonial and revolutionary movements of the postwar era. Bardawil interweaves Charara's own intellectual trajectory and writings with those of others, holding the theoretical discussions in close relation with the sticky specificity of the internecine solidarities and fissions that characterized revolutionary movements of the time - specificity that has been all but lost for lack of formal archives. Bardawil's use of both historical and ethnographic methods - a fieldwork in theory - pulls the analysis from a strictly theoretical register so that it might better be operationalized in terms of practice. His argument responds to what he refers to as the "metropolitan unconscious" within Middle Eastern studies that attempted to encapsulate and reify Leftist Arab thought outside of its context. In considering these intellectuals "at home," Bardawil reworks the typical asymmetrical relationship that used Continental critical theory to pull apart and simplify postwar revolutionary Arab thought in order to place intellectuals from both traditions in conversation with one another"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Socialism -- Lebanon -- History; New Left -- Lebanon -- History; Lebanon -- Politics and government -- 1946-; Electronic books